The effect of root canal treatment on oral health-related quality of life: Clinical trial - Abdulsamad Turki Ezzat; Abdulwahab F Nagro; Ahmed T Fawzy; Omair M Bukhari (Wolters Kluwer Medknow Publications, 2021)
Introduction: The awareness of patient-centered outcomes regarding the sequel of endodontic therapy in everyday life is limited. This study aimed to quantify the impact of root canal treatment in one visit compared to root canal treatment in multiple visits on oral health-related quality of life (OHRQoL). Material and Methods: This is a controlled clinical trial, in which 32 patients were included; the age range was 16-60 years. At the patient's convenience, participants were divided into two groups: the first group received a single-visit treatment and the other group received a multiple-visit treatment. Conventional endodontic treatment was performed for indicated teeth by undergraduate dental students in a single visit or multiple visits. OHRQoL was recorded using an Arabic Oral Health Impact Profile (OHIP) questionnaire. Results: A total of 32 patients, with a mean age of 30.5 (SD = 8.2), received root canal treatments and filled OHIP questionnaire. Male patients composed 50% of the sample. The majority of the patients had a high school education (75%). Single-visit root canal treatment significantly improved OHRQoL by 7.6 points (P = 0.001) and multiple visits by 8 points (P = 0.001). Conclusion: Both single and multiple visits endodontic treatments equally improved OHRQoL.